Geochemical analysis of water objects of the left bank of the basin of river living under the West-Kazakhstan region (Journal of Geography and Environmental Management, 2017)
In this article, the actual to date problem of anthropogenic impact and its influence on the river basin is considered, which leads to an increase in the number of chemical elements in the river basin. This leads to pollution, unforeseen situations in the state of the environment, harmful effects on water bodies and negative effects on humans. As a result of exposure to polluted environment toxic substances with toxic elements – environmental pollutants appear. Such pollutants include lead, cadmium, copper, zinc, iron, etc. The main danger of modern anthropogenic influence lies in the inconsistency of the boundless needs of mankind and the almost boundless scientific and technical possibilities of influence on nature and the limited possibilities of nature itself. In this regard, there is a need for a geochemicalanalysis of water bodies in the river basin in order to analyze, regulate and prevent pollution at the initialstage of their development in a certain territory. In this case, the object of the study is the territoryof the left bank of the Zhayik river basin with in the Western Kazakhstan region. Therefore, the articleshows a geochemical analysis of water objects on the left bank of the Zhayik river basin, obtained fromsamples of natural surface water from fourteen key sections describing the characteristics of the chemicalcompounds content in water bodies. The studies were carried out on the basis of the data of a testinglaboratory, during investigations, the excess of the maximum permissible concentration in water bodieswas determined for such chemical elements as Ca, Mg, SO42-, Mn, Fe, Na and K, chlorides and stiffness.